Therapeutic Communication By Spiritual Guides To Reduce Patient Anxiety Facing Childbirth At Qolbu Insan Mulia Batang Hospital - Indah Puji Astuti (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
Pregnant patients experience various changes, both physically and psychologically. With these changes, pregnant patients are expected to be able to keep themselves healthy for the sake of smooth delivery. In the hospital, a spiritual guide provides psychological services, guides in performing prayers, and helps find solutions to the problems faced by patients. This service is very important as an effort to accelerate the patient's recovery, so a spiritual guide must be competent in his field.The ministry of a spiritual director has a very important role in the patient's recovery. In the communication process, including counseling relationships, there are two elements to body language. Therapeutic communication is communication that is planned and carried out to assist the healing or recovery of the patient. This communication is generally more intimate because it has a purpose, and focuses on the patient who needs help. when conducting Islamic guidance and counseling several methods and techniques can be developed, namely Ersyad Nafsiyah, Ersyad Fardhiyah, and Ersyad Fiah Qolilah. All methods and Islamic counseling guidance are delivered in the form of brief focused counseling, namely counseling in hospitals carried out by counselors in a brief manner. Communication that is more effectively used by spiritual guides is therapeutic. Therapeutic is an adjective associated with the art of healing. Therapeutic communication is communication that is planned and carried out to help the healing or recovery of the patient. This communication is generally more intimate because it has a purpose, focusing on patients who need help. spiritual guides actively listen and respond to patients by showing an attitude of acceptance and understanding so that they can encourage patients to talk openly about themselves. Besides that, it can also help patients to see and pay attention to what they were not aware of before.